Clinical outcomes of a diabetes education program for patients with diabetes mellitus in the Micronesian community in Hawaii - Mok Thoong Chong (Wolters Kluwer Medknow Publications, 2016)
Objective: Hawaii has diverse population made up of a cultural mix of different races. Due to different cultural and social influences and language barrier, many of the under-served population who migrated to Hawaii and having diabetes mellitus may be susceptible to long-term complications due to uncontrolled hyperglycemia and medication nonadherence. The purpose of this study was to evaluate the impact of a diabetes education program on the clinical outcomes in patients with diabetes mellitus in the Micronesian community of Hawaii. Methods: This study included patients over age 18 years, with a diagnosis of type 2 diabetes mellitus. The diabetes education program was customized for its weekly classes to fit to the under-served population. Data were collected on participants on the 1 st day and then 6 months after attending the education program. Data on primary and secondary endpoints were collected and analyzed. Findings: The mean glycosylated hemoglobin A 1c , fasting blood glucose, and triglyceride levels of participants fell significantly from baseline after attending the diabetes education program for 6 months. No significant changes were observed in other secondary outcomes during the study time period. Conclusion: Based on our findings, the diabetes education program that was tailored to the Micronesian population was successful in achieving glycemic goals, enhancing medication adherence, improving clinical outcomes, and also preventing long-term complications among its participants.